Analisa Variasi Putaran Friction Welding Terhadap Kekerasan Logam Aluminium Paduan Seri 1100-H18 - Daryono; Dwi Handoko; Topan Prihantono; Ady Setiawan (Politeknik Negeri Cilacap, 2022)
Research in aluminum splicing continues to be improved, so that the joining process becomes easier and to increase hardness. Friction stir welding (FSW) aluminum joining process. The purpose of this study was to find out more clearly about the mechanical properties of the hardness of the specimen. The material used is aluminum alloy 1100-H18 series. The research method is friction welding with Vertical Milling as a turning tool. The tests were carried out in different rounds, namely; 660 rpm; 1115 rpm; 1750 rpm and 2720 rpm with a fixed tool feed rate of 20 mm/minute. The results of the Vickers test show that the hardness of the Base Metal (BM) area at 660 rpm is the highest at 101.4 and the lowest is 97.62 at 1115 rpm. The highest average hardness value of 94.98 occurs at 1115 rpm and the lowest is 75.18 at 2720 rpm. A significant effect on the hardness of the specimen due to the rotational speed of the tool spindle (electrode), the higher the rotation, the higher the heat generated and the rate of The slow cooling in the HAZ and SZ regions will be greater, as a result the hardness in the HAZ and SZ regions will decrease.